Numerical Study on Heat Transfer Characteristics of the 36V Electronic Control Unit System for an Electric Bicycle - Gihan Ekanayake; Mahesh Suresh Patil; Jae-Hyeong Seo; Moo-Yeon Lee (Energies, 2018)
The objective of this study was to numerically investigate the heat transfer characteristics of a 36V electronic control unit (ECU) system of an electric bicycle and to validate the experimental data. The temperatures of the ECU heatsink, seven metal-oxide-silicon field effect transistors (MOSFETs) and two capacitors of the 36V ECU system were numerically derived under variable operating conditions including power dissipation, thermal grease, ambient temperature and heatsink material, to analyze the heat transfer characteristics. When the thermal conductivity of the thermal grease increased from 0.01 W/m °C to 3.0 W/m° C, the temperatures of the seven MOSFETs and the two capacitors decreased by 51.245% and 3.58%, respectively. When the total power dissipation increased from 2.57 MW/m3 to 4.26 MW/m3, the temperatures of the ECU heatsink, seven MOSFETs and the two capacitors increased by 20.95%, 30.31% and 21.54%, respectively. Furthermore, increasing the ambient temperatures from 30 °C to 40 °C resulted in an increase in the temperatures of the ECU heatsink, MOSFET and capacitor by 24.75%, 9.93% and 22.04% respectively.. These numerically derived temperatures for the MOSFET and the ECU heatsink were validated with the experimental results within a range of 7.2% and 1.7%, respectively. This confirmed that the applied numerical model was valid.